ACUTE RESPIRATORY VIRAL INFECTIONS PROPHYLAXIS IN ORGANIZED GROUPS OF CHILDREN: MEANS AND EFFICACY - N. V. Ermilova; E. Yu. Radtsig; M. R. Bogomilskiy; E. P. Selkova; N. A. Gudova (Вопросы современной педиатрии)
In the article we observe questions of acute respiratory infections prophylaxis in organized groups of children along with means of boosting of body ant-infectious protection. We review efficacy data for Ocilococcinum, Anaferon for children, Grippferon used as means of seasonal prophylaxis of repiratory diseases in organized groups of children.Key words: prophylaxis, children, complex homeopathic medications.